Spatial structure and factors determining tree mortality in Beninese forest formations - ATINDOGBE, GILBERT; Laly, Finagnon G.; Adjinannoukon, Arios; FONTON, HOUÉDOUGBÉ NOËL (My University, 2021)
Dead wood plays an important role in the functioning of forest ecosystems through nutrient cycles, soil fertility balance and temporary carbon storage. This research evaluates the dead wood potential, spatial structure of dead trees and factors influencing tree mortality in natural woodlands in Benin. Data were collected in eleven square plots of 10,000 m2, established in six classified forests and hunting areas of the W and Pendjari national parks. The spatial structure was investigated using Ripley's K function, and a multiple regression with variable selection allowed the identification of the biotic and abiotic factors that have an effect on dead wood density in the study areas. The density of dead wood was 32 stems/hectare, while mean quadratic diameter and basal area were 17.2 cm and 0.88 m2.ha-1, respectively. There was random and regular spatial distribution of dead trees without a positive interaction between dead and living trees, thereby pointing to fire as the main factor of tree mortality. Other factors influencing tree mortality included attacks by saproxylic animal species and other wood pests, and senescence. This study suggests that an integration of dead trees in management plans may be essential for the proper functioning of Benin's forest ecosystems.
Keywords: Dead wood; spatial structure; causes of mortality; Benin. Arbres morts; structure spatiale; causes de mortalité; Bénin.